Use and perceived benefits of mouthwash among Malaysian adults: an exploratory insight - Siddiqui, Mohammad Jamshed Ahmad; Mitha, Shahid; C., E. Tan; Koh, M.; Babar, Muneer Gohar; Rajiah, Kingston; Jamshed, Shazia Qasim; Hassali, Mohamed Azmi (Elsevier, 2014)
This study aimed to explore the use and perceived benefits of mouthwash among Malaysian adults. Method: This is a cross-sectional study which was conducted in public places around the states of Selangor and Penang, Malaysia. It is a questionnaire-based study which was conducted as face-to-face interview. A convenience sample of 792 mouthwash users was recruited in 2013 in an ethically approved study (International Medical University). The study instrument was formulated on the basis of literature search and subjected to 20 experts for validation purpose. A pilot study was conducted to compute Cronbach Alpha (0.78). Data was entered into PASW version 20. Descriptive and inferential statistics were applied. Results: A response rate of 99% was achieved. More than two third of the respondents are female, suggesting women are more likely to use mouthwash (n ¼486; 61.8